Treatment with ActRIIB-mFc Produces Myofiber Growth and Improves Lifespan in the Acta1 H40Y Murine Model of Nemaline Myopathy - Tinklenberg, Jennifer (Am J Pathol, 2016)
Nemaline myopathies (NMs) are a group of congenital muscle diseases caused by mutations in at least 10 genes and associated with a range of clinical symptoms. NM is defined on muscle biopsy by the presence of cytoplasmic rod-like structures (nemaline rods) composed of cytoskeletal material. Myofiber smallness is also found in many cases of NM and may represent a cause of weakness that can be counteracted by treatment. We have used i.p. injection of activin type IIB receptor (ActRIIB)–mFc (an inhibitor of myostatin signaling) to promote hypertrophy and increase strength in our prior murine work; we therefore tested whether ActRIIB-mFc could improve weakness in NM mice through myofiber hypertrophy. We report a study of ActRIIB-mFc treatment in the Acta1 H40Y mouse model of NM. Treatment of Acta1 H40Y mice produced significant increases in body mass, muscle mass, quadriceps myofiber size, and survival, but other measurements of strength (forelimb grip strength, ex vivo measurements of contractile function) did not improve. Our studies also identified that the complications of urethral obstruction are associated with mortality in male hemizygote Acta1 H40Y mice. The incidence of urethral obstruction and histologic evidence of chronic obstruction (inflammation) were significantly lower in Acta1 H40Y mice that had been treated with ActRIIB-mFc. ActRIIB-mFc treatment produces a mild benefit to the disease phenotype in Acta1 H40Y mice.